Persepsi Guru Pamong Tentang Kemampuan Mahasiswa S1 Tata Boga dalam Kegiatan Program Pengalaman Lapangan Kependidikan di SMK Pariwisata Sumbar - Dewi, Ayu Prastika; Elida, Elida; Gusnita, Wiwik (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
The purpose of research is to describle the teacher tutor perception about the personal and social abilities S1 culinary student in program work field education experience in vocational school in West Sumatera Tourism. The method of this research is using ex post facto with the total population are 43 people. The research implemented in 9 vocational school in West Sumatera for a month. The results of this research found that generally the perception of teacher tutor about the ability S1 culinary student in category as sufficiently with percentage 62,79%. Further, indicator the ability of personality in category sufficiently with percentage 60,46%. Then, to Indicator social ability in category sufficiently with percentage 55,81%.Keyword : Perception Teacher Tutor, Ability College Student PPLK